Facilitating collaborative capabilities for future work: What can be learnt from interprofessional fieldwork in health - Brewer, Margo; Flavell, Helen (2018)
There is growing pressure in higher education to develop graduates with the capabilities to work effectively in collaborative, interdisciplinary teams to solve the key issues facing humankind. For many years, health has been pioneering interprofessional education as the means to deliver professionals with capacity to work together to deliver high quality, cost-effective, client-centered care. This paper reports on an explorative case study where interviews were undertaken with ten students from different professions who had experienced interprofessional education at three different community sites. The learning was informed by an adapted version of contact hypothesis for use in interprofessional education combined with adult learning principles. Four interrelated metathemes were identified: space and time, informality and independence, which resulted in a more holistic approach to practice. Results suggest that the contact hypothesis, with consideration of contact variables, has the potential to improve the quality of interdisciplinary group interaction.